Abu Ali Ibn Sina (369-429AH/980-1037CE) - Akhmetova, Elmira (Pelanduk Publications Sdn. Bhd., 2018)
This chapter discusses the contributions of Ibn Sina to the development of Islamic civilisation by highlighting his ideas, philosophy, achievements in medicine and life.